Building Thermal Comfort Research Based on Energy-Saving Concept. (25th August 2021) - Xue, Feiran; Zhao, Jingyuan
Abstract : Under the trend of building green and comfortable development, effective control of building energy consumption has become one of the problems that countries are actively facing to solve. People's demand for residential buildings has changed from the past survival type to a comfortable and livable type. The high level of heating energy consumption is worthy of in-depth study. In order to reduce energy consumption, realize the mapping of energy-saving concepts in buildings, and understand the energy consumption of different building materials and the influence of external factors on human thermal comfort, this book has conducted research on building thermal comfort based on energy-saving concepts. First of all, this article introduces the concept and application mode of energy-saving concepts in buildings and the concept of thermal comfort and the SET index of standard effective temperature, including the two-node model and the algorithm involved in the Fanger heat balance equation. In the experimental part, a model based on the concept of energy saving was designed to predict and analyze the energy consumption and thermal comfort effects of the building. In the analysis part, a comprehensive analysis of the effects of temperature, humidity, wind speed, and gender on thermal comfort, methods to improve thermal comfort, cumulative load changes with the heat transfer coefficient of windows, and the effects of windows of different materials on energy consumption was performed. At the same temperature, the wind speed is different, and the degree of heat sensation is also different. When the wind speed is 0.18 m/s and the temperature is 28°C, the thermal sensation is 0.32, and the human sensation is close to neutral. When the wind speed increases to 0.72 m/s, the heat sensation drops to −0.45, and the human body feels neutral and cool. It can be seen that the increase in wind speed has a certain compensation effect on the thermal sensation of the human body. When the wind speed does not change, increase the air temperature. For example, when the wind speed is 0.72 m/s, the temperature is 28°C, and the thermal sensation is −0.45, and when the temperature is increased to 29°C, the thermal sensation is 0.08, which shows that the temperature is improving the thermal sensation of the human body which has a certain offsetting effect. By studying the thermal comfort of buildings based on energy-saving concepts, it is possible to obtain the effect of external factors on thermal comfort, thereby optimizing building materials and using building materials with lower heat transfer coefficients to reduce heating energy consumption.